Naturally Occurring Polyphenolic Glucosidase Inhibitors. Issue 3 (4th February 2015) - Yang, You; Lian, Gaoyan; Yu, Biao
Abstract: Polyphenols, which are abundantly distributed in plants such as fruits, vegetables, and tea, constitute a large group of aromatic compounds, mainly including phenolic acids and flavonoids. These natural metabolites have been demonstrated to possess a wide range of biological activities associated with health benefits, including the α‐glucosidase inhibitory activity. In contrast to the classical α‐glucosidase inhibitors, e.g., aza/imino sugars, polyphenols serve as a new type of α‐glucosidase inhibitor with different, yet unknown, mechanisms of action, which could lead to novel dietary supplements and therapeutic agents for the prevention and treatment of metabolic disorders. In this review, we report a collection of 137 naturally occurring phenolic acids and flavonoids with α‐glucosidase inhibitory activities. Abstract :